2005
DOI: 10.1002/jbm.b.30200
|View full text |Cite
|
Sign up to set email alerts
|

Tricalcium phosphate and glutaraldehyde crosslinked gelatin incorporating bone morphogenetic protein—A viable scaffold for bone tissue engineering

Abstract: Bone defects caused by various etiologies must be filled with suitable substances to promote bone repair. Autogenous iliac crest graft is most frequently used, but is often associated with morbidities. Several bone graft substitutes have been developed to provide osteoconductive matrices as well as to enhance osteoinductivity. A tricalcium phosphate and glutaraldehyde crosslinked gelatin (GTG) scaffold, incorporated with bone morphogenetic proteins (BMPs), was developed to provide an alternative mean of bone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…An in vitro study with primary rat calvarial osteoblasts showed an increased cellular activity in the BMP-loaded samples [392]. Other researchers investigated BMP-2-loaded porous b-TCP/gelatin biocomposites (porosity 95%, average pore size 180-200 lm) [402] and confirmed the precious study.…”
Section: Tcp-based Biocompositesmentioning
confidence: 59%
See 3 more Smart Citations
“…An in vitro study with primary rat calvarial osteoblasts showed an increased cellular activity in the BMP-loaded samples [392]. Other researchers investigated BMP-2-loaded porous b-TCP/gelatin biocomposites (porosity 95%, average pore size 180-200 lm) [402] and confirmed the precious study.…”
Section: Tcp-based Biocompositesmentioning
confidence: 59%
“…Besides, they are faster resorbed in vivo. 5 Therefore, these calcium orthophosphates were used instead of HA to prepare completely biodegradable biocomposites [376][377][378][379][380][381][382][383][384][385][386][387][388][389][390][391][392][393][394]. For example, a biodegradable and osteoconductive biocomposite made of b-TCP particles and gelatin was proposed [385].…”
Section: Tcp-based Biocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another research group prepared biocomposites of cross-linked gelatin with β-TCP, and both a good biocompatibility and bone formation upon subcutaneous implantation in rats were found. 469 Yang et al 474 extended this to porous (porosity ~75%) β-TCP/gelatin biocomposites that also contained BMP-4. Porous β-TCP/ alginate-gelatin hybrid scaffolds that were cell-compatible and possessing some osteoinductive properties were aso prepared and successfully tested in vitro.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%